Analisis Kenaikan Temperature pada Turbine Guide Bearing untuk Pemeliharaan Periodik Unit 2 PLTA Maninjau - Pratama, Bagas Adi; Mukhnizar, Mukhnizar; Zulkarnain, Zulkarnain; Selviyanty, Veny; Abu, Risal (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Turbine Bearing is a piece of equipment used to keep the shaft rotating about its axis or to keep a linearly moving component on track. The operation at PLTA Maninjau also makes use of a Turbine Bearing with a Journal Bearing type. The turbine bearing of the Maninjau hydropower plant experienced an abnormality, with the bearing temperature rising from 60°C to 80°C. Using the fishbone diagram method and failure mode and effects analysis, the authors conducted a root cause analysis of the causes of the increase in turbine bearing temperature in this study (FMEA). The cause of the increase in. The cause of the increase in the temperature of the turbine bearing unit 2 of the Maninjau Hydropower Plant was found to be a misalignment caused by a small bearing clearance of 0.2 mm, which should have been 0.4 mm according to the design value, after conducting research using the observation method through data collection and data processing. And reduced cooling water effectiveness from 18.41% to 1.15%. As a result, corrective maintenance on Maninjau Hydropower Unit 2 is required.